Europium-doped ruthenium oxide nanostructures: Hydrothermal synthesis, structural characteristics and dielectric performance - Macit, Cevher Kursat; Gurgenc, Turan; Gurgenc, Ezgi; Biryan, Fatih; Ilkilic, Cumali; Ozkan, Betul Cicek (Springer Heidelberg, 2025)
Eu-doped RuO2 nanostructures with 1, 3, and 5 wt.% doping were synthesized via a hydrothermal method at 180 degrees C for 12 h followed by annealing at 450 degrees C. XRD confirmed the rutile tetragonal phase, with diffraction peak shifts toward higher 2 theta values reflecting lattice contraction from oxygen vacancy formation. The average crystallite size remained in the nanoregime (14-16 nm), ensuring structural stability. FE-SEM revealed a morphological transition from spherical to elongated grains with enhanced connectivity at higher Eu levels, while EDX mapping confirmed uniform Eu distribution. FT-IR and Raman spectra identified Eu-O vibrations, lattice strain, and defect-related modes, consistent with substitutional doping. XPS analysis confirmed the Eu3+ oxidation state and an increasing contribution from defect-related oxygen species. Dielectric testing demonstrated a marked increase in dielectric constant from 17.75 (pure RuO2) to 23.60, 33.07, and 43.73 at 1, 3, and 5 wt.% Eu, respectively, representing a similar to 146% improvement at the highest doping. Dielectric loss rose from 2.46 to 14.46 with Eu addition, while AC conductivity increased from 1.09 x 10(-8) S/cm (pure) to a maximum of 2.89 x 10(-8) S/cm at 3 wt.% Eu before decreasing to 1.46 x 10(-8) S/cm at 5 wt.% due to defect clustering. These findings show that controlled Eu doping effectively tailors oxygen vacancy concentration, defect dipole density, and interfacial polarization, enabling significant enhancement of dielectric performance and tunable conductivity. Consequently, Eu-modified RuO2 is a promising candidate for high-k dielectrics in capacitors, memory devices, and multifunctional optoelectronic systems. [GRAPHICS] .
Keywords: Nanomaterial; Hydrothermal; Ruthenium oxide; Rare earth element; Dielectric